Optimization of the ultrasound-assisted extraction process to obtain a citric acid-rich extract from citrus peels - Fernandes, Filipa Alexandra (2022)
Citrus fruits belong to the most consumed group of fruits worldwide and, in most cases, their peels are discarded as by-product, used for the manufacture of animal feed or simply disposed of as waste.1,2 However, scientific studies have shown that these by-products are rich in high added-value compounds, including phenolic compounds and organic acids.1,3 Fernandes et al. (2020) demonstrated the effectiveness of citric acid as a natural preservative in a nutraceutical product, concluding that it has a strong potential to be used in the food industry as an alternative to artificial preservatives.4 The objective of this work was to optimize the ultrasound-assisted extraction of citric acid from citrus (orange, lemon and lime) peels using the response surface methodology (RSM). Orange, lemon, and lime peels were frozen, lyophilized and reduced to ~20 mesh particle size. For the extraction optimization, a central composite design coupled with RSM was implemented by combining five levels of the independent variable’s ethanol concentration (0–100%, v/v), time (2–45 min) and ultrasonic power (50–500 W). The UAE was performed using a sonicator system with a titanium probe. The citrus peel samples (~1 g) were placed in a beaker with 50 mL of solvent and processed according to the experimental design at room temperature. The levels of citric acid were determined by UFLC-PDA and used as a response variable. Design-Expert software was used for regression and graphical analysis of the data. The developed theoretical models were successfully fitted to the experimental data, statistically validated based on high F-values and R2 values and used to predict the optimal conditions that maximize the recovery of citric acid from the citrus peels. Citric acid was identified and quantified in two by-products, orange and lime peels, with the optimal processing conditions yielding about 10 and 8 g of this compound per 100 g of dry peels, respectively. Thus, to obtain a higher extraction yield, the citric acid from the orange peels must be extracted with short times, high ultrasonic powers and the extraction solvent must contain a low ethanol concentration. For lemon peels, citric acid was not detected in some runs of the experimental design, so it was not possible to construct a predictive model. It was concluded that, with this extraction technique and applied methodology, citrus peels, particularly of orange, are a good source of citric acid. The present work contributes to the valorization of citrus by-products through their recycling into a natural food ingredient. However, a deeper analysis of these ingredients is necessary to allow the industries to implement sustainable extraction techniques and to use citric acid recovered from citrus as a food preservative.